Sosialisasi pengelolaan keuangan keluarga sebagai upaya meningkatkan kesejahteraan - Putri, Arie Rachma; Al Hakim, Humairoh; Nurfika, Dita; Syifa, Dea (Tintamas: Jurnal Pengabdian Indonesia Emas, 2025)
This Community Service Activity aimed to enhance financial literacy and family financial management skills among mothers in the Klaten Pimpinan Daerah Aisyiyah Economic and Employment Council. The program was motivated by the low level of understanding regarding financial planning, recording, and control, which affects family welfare. Thirty participants joined enthusiastically, engaging in lectures, discussions, case studies, and hands-on budgeting and financial training. Pre-and post-test evaluation revealed improvements across all indicators, with the most significant increases in preparing regular budgets (15.7%) and recording income and expenses (8.3%). More minor improvements were noted in prioritizing basic needs (4.1%) and managing expenses (0.9%), likely because many participants, as housewives, were already accustomed to these practices in daily life. In terms of effectiveness, the activity successfully improved participants’ knowledge and skills. From an efficiency perspective, it was carried out optimally despite limited time. Moving forward, this initiative is expected to foster positive financial habits within families and strengthen household economic resilience through ongoing mentoring.